Are the Effects of Homeopathy Attributable to a Statistical Artefact? A Reanalysis of an Observational Study. (15th December 2013) - Lüdtke, Rainer; Willich, Stefan N.; Ostermann, Thomas
Abstract : Background . Cohort studies have reported that patients improve considerably after individualised homeopathic treatment. However, these results may be biased by regression to the mean (RTM). Objective . To evaluate whether the observed changes in previous cohort studies are due to RTM and to estimate RTM adjusted effects. Methods . SF-36 quality-of-life (QoL) data from a German cohort of 2827 chronically diseased adults treated by a homeopath were reanalysed by Mee and Chua's modified t -test. Results . RTM adjusted effects, standardized by the respective standard deviation at baseline, were 0.12 (95% CI: 0.06–0.19, P < 0.001 ) in the mental and 0.25 (0.22–0.28, P < 0.001 ) in the physical summary score. Small-to-moderate effects were confirmed for the most individual diagnoses in physical, but not in mental component scores. Under the assumption that the true population mean equals the mean of all actually diseased patients, RTM adjusted effects were confirmed for both scores in most diagnoses. Conclusions . Changes in QoL after treatment by a homeopath are small but cannot be explained by RTM alone. As all analyses made conservative assumptions, true RTM adjusted effects are probably larger than presented.